TEMPORARY PACE MAKERS IMPLANTATION: DO WE NEED FLUOROSCOPY? - Shah, Bakhtawar; Awan, Zahid Aslam (Journal of Ayub Medical College Abbottabad, 2015)
Background: Temporary pace maker (TPM) implantation is done mostly in emergency with assistance of fluoroscopy. Fluoroscopy has various constrains which may delay the procedure at different occasion. We are going to share our experience in TPM implantation without fluoroscopy from internal jugular vein. Methods: The case series study was conducted in Hayatabad Medical complex Peshawar from January 2011 to November 2011. Internal jugular vein was cannulated with 6 French sheaths in the supra-clavicular region with modified Seldinger technique. TPM wire connected to the TPM device and advanced in the sheath to the right ventricle. Position was confirmed from captured beat on monitor. There was no need of repositioning and lead remains stable. Results: Total 122 TPM leads were implanted in the study period. All patients were implanted from internal jugular vein. There were 71 male and 51 female patients. Among these patients 55 were in hemodynamically unstable state. The average time of implantation was less than 10 minutes. There was failure in one case. So the overall success rate was 99.180%. Conclusion: TPM implantation from the internal jugular vein even without fluoroscopy is safe, less time consuming and convenient. Keywords: Temporary pace maker (TPM), Fluoroscopy, internal jugular vein (IJV)